Pancreatic pain - Nechutova, Hana; Dite, Petr; Hermanova, Marketa; Novotny, Ivo; Martinek, Arnost; Klvana, Pavel; Kianicka, Bohumil; Soucek, Miroslav (Wiener medizinische Wochenschrift (1946), 2014)
Pain is a common symptom of many diseases. Recently, the pain has been classified and analyzed exactly. Its particular components/types are described to the maximum of their depths and details. That is why each particular pain present in a specific disease (pancreatopathies included) has to be treated according to the presence of the specific type of pain. In diseases of pancreas, there are nociceptive, neuropathic, and inflammatory components of pain participating, frequently. Especially long-lasting, not well-controlled pain sets off the process of neuromodulation. The recent pioneering applications/administrations of various neuromodulatory therapeutic approaches represent the promising discoveries for the treatment of long-term, severe, drug-resistant pain syndromes, including chronic pancreatitis. In this article, we summarized the characteristics of pain, the therapeutic strategy, and algorithms of analgesic treatment (in general and applied for pancreatopathies), including new therapeutic trends and approaches.
Keywords: chronická pankreatitida; nociceptory; chronická bolest; pankreas; mediátory zánětu; Neuralgia; neurotransmiterové látky; Pancreas; Chronic Pain; Nociceptors; Neuronal Plasticity; Pain Management; Neurotransmitter Agents; lidé; Pancreatic Diseases; management bolesti; Humans; Pancreatitis, Chronic; Inflammation Mediators; nemoci slinivky břišní; neuroplasticita; neuralgie